2020
DOI: 10.1039/c9nj05965b
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the kinetics and molecular mechanism of the degenerate Cope rearrangement of bullvalene

Abstract: The kinetics and molecular mechanism of the gas phase degenerate Cope rearrangement (DCR) of bullvalene have been investigated by applying quantum mechanical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
7
2
Order By: Relevance
“…In agreement with the findings of Gimarc et al [7] . the activation energy for DCR of hypostrophene is larger than that of bullvalene [3] . The lack of experimental results has made it impossible to determine the degree of accuracy of CBS kinetic data.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…In agreement with the findings of Gimarc et al [7] . the activation energy for DCR of hypostrophene is larger than that of bullvalene [3] . The lack of experimental results has made it impossible to determine the degree of accuracy of CBS kinetic data.…”
Section: Resultssupporting
confidence: 85%
“…The lack of experimental results has made it impossible to determine the degree of accuracy of CBS kinetic data. According to the C−C single bond dissociation energy (347 kJ.mol −1 ) and stabilization energy due to the delocalization of the π electrons in allylic radicals (88 kJ.mol −1 ) in the homoaromatic transition structure, the activation enthalpy is estimated to be about 171 kJ.mol −1 [3,38] . The value of the calculated activated enthalpy from the CBS energies revealed that the stabilization energy because of the interactions between the allyl moieties in the homoaromatic transition structure for DCR of hypostrophene is ∼85 kJ.mol −1 , which is smaller than that value for DCR of bullvalene [3] .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations